2020
DOI: 10.1097/jom.0000000000001919
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of Job Demands and Job Control and Future Trajectories of Sickness Absence and Disability Pension An 11-year Follow-up of Two Million Employees in Sweden

Abstract: Objective: The aim of this study was to examine the association between combinations of job demands/control and future sickness absence (SA) and disability pension (DP) trajectories over 11 years. Methods: A population-based prospective cohort study of female (n = 1,079,631) and male (n = 1,107,999) employees in 2001. With group-based trajectory analysis, we modeled the trajectories of annual mean SA/DP days in 2002 to 2012. We predicted trajectory memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…In our study, the proportion of workers that did not have Norwegian as their mother tongue was stable between the trajectory groups. This contrasts Swedish studies [ 26 , 29 ], which found that trajectories with high SA days had more individuals born outside Sweden and the EU.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…In our study, the proportion of workers that did not have Norwegian as their mother tongue was stable between the trajectory groups. This contrasts Swedish studies [ 26 , 29 ], which found that trajectories with high SA days had more individuals born outside Sweden and the EU.…”
Section: Discussioncontrasting
confidence: 86%
“…Our findings regarding different characteristics between all trajectory groups corroborate previous studies. Trajectory groups characterised by a high number of SA days tended to be overrepresented by women [ 2 , 6 , 26 , 29 ], individuals with more days on sick leave the previous year [ 26 , 29 ], and individuals who tended to score higher on pain intensity [ 3 , 6 ], multisite pain [ 2 , 6 , 7 , 28 ], and depressive symptoms [ 3 , 28 ]. Although some studies have reported higher proportions of smokers in high SA trajectories [ 2 , 6 , 28 ], we were only able to identify this in the ‘moderate persisting’ trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…We also found a much clearer differentiation by sex than previous studies have found in the general population, especially regarding the level of job control, where women were predominantly located in occupations with low control and men in occupations with high control. This is not as clear in studies of the entire population 29,36 . The sex differences in the level of control could also possibly contribute to the sex differences in SA/DP; however, this needs to be investigated further.…”
Section: Discussionmentioning
confidence: 96%
“…This is not as clear in studies of the entire population. 29,36 The sex differences in the level of control could also possibly contribute to the sex differences in SA/DP; however, this needs to be investigated further. That change of occupation, branch of industry, or sector in 2016 was not strongly associated with SA/DP could be related to that most people were still in the same occupation, in the trade and retail industry and private sector.…”
Section: Discussionmentioning
confidence: 99%
“…It is understandable that SA due to mental diagnoses constituted an independent cluster since among white-collar workers that is the most common specific diagnostic group of SA and/or DP 1 37 39–41. This cluster was more common among women, 34–44 years, less than tertiary educated, low-income earners who worked in education, care, nursing and social industry, and had a long SA spell in 2012, which are known risk factors for SA due to mental diagnoses in general 42 43…”
Section: Resultsmentioning
confidence: 99%